Digital Service Experience Moderating Satisfaction on Loyalty: Generational Comparison in Indonesian Fashion MSMEs - Saputra, Al Mahfud; Maihani, Syarifah; Rizkina, Azka; Mukhdasir, Mukhdasir (Business Review and Case Studies, 2025)
Background: Micro-, small-, and medium-sized enterprises (MSMEs) in Indonesia’s fashion sector face growing challenges in building consumer loyalty across generational segments with diverse digital consumption patterns. While previous studies have investigated satisfaction and loyalty in metropolitan markets, few have explored these relationships within non-metropolitan MSMEs, leaving a theoretical gap in understanding how Digital Service Experience (DSE) moderates such dynamics in regional contexts. Purpose: This study examines the effects of Product Quality (PQ) and Brand Image (BI) on Customer Satisfaction (CS) and Customer Loyalty (CL) while analyzing the moderating role of Digital Service Experience (DSE) across Generations Y and Z. By addressing this gap, this study extends existing theories of consumer behavior to intergenerational loyalty formation in emerging digital markets. Design/methodology/approach: A quantitative survey was conducted with 600 respondents (300 Generation Y and 300 Generation Z), who purchased local fashion MSME products through digital platforms. Data were analyzed using Partial Least Squares–Structural Equation Modelling (PLS-SEM), Moderated Regression Analysis (MRA), and Multi-Group Analysis (MGA) to test direct, indirect, and moderating relationships, as well as generational differences. Findings: The findings revealed distinct generational patterns in loyalty formation. PQ has a stronger impact on CS and CL among Generation Y, which values functionality and reliability. In contrast, BI influences Generation Z more strongly, reflecting emotional and identity-based motivations. Customer Satisfaction mediated the effects of PQ and BI on loyalty in both groups. Digital Service Experience enhances loyalty and strengthens the CS–CL link, especially among Generation Z, although it does not significantly alter the PQ–CL or BI–CL relationship. Conclusion: Customer satisfaction is the principal determinant of loyalty, while digital service experience enhances, but does not replace, the fundamental influence of product quality and brand image. The integration of the Theory of Planned Behavior (TPB) and Expectation Confirmation Theory (ECT) bridges theoretical and contextual gaps, providing a robust framework for understanding generational loyalty in MSME settings. Originality/value: This study provides novel empirical evidence of cross-generational consumer behavior in non-metropolitan MSMEs. It extends the TPB–ECT framework to incorporate digital service experience and highlights the actionable managerial implications for enhancing competitiveness and loyalty in the digital economy. Keywords: product quality, brand image, digital service experience, customer satisfaction, customer loyalty